Abundance of Escherichia coli F1-ATPase molecules observed to rotate via single-molecule microscopy with gold nanorod probes - York, J; Spetzler, D; Hornung, T; Ishmukhametov, R; Martin, J; Frasch, WD (Springer, 2007)
The abundance of E. coli F1-ATPase molecules observed to rotate using gold nanorods attached to the γ-subunit was quantitated. Individual F1 molecules were determined to be rotating based upon time dependent fluctuations of red and green light scattered from the nanorods when viewed through a polarizing filter. The average number of F1 molecules observed to rotate in the presence of GTP, ATP, and without nucleotide was ∼50, ∼25, and ∼4% respectively. In some experiments, the fraction of molecules observed to rotate in the presence of GTP was as high as 65%. These data indicate that rotational measurements made using gold nanorods provide information of the F1-ATPase mechanism that is representative of the characteristics of the enzyme population as a whole.